Human resource management best practices and firm performance: a universalistic perspective approach - Beh, Loo-See; Loo, Leap-Han (Serbian Journal of Management, 2013)
The universalistic perspective of human resource management practices perceives that a set of practices can achieve competitive advantage and firm performance. This study sought to investigate the relationship between best human resource practices and firm performance. A descriptive survey research design was used to gather primary data using self-administered questionnaire. The study population (n=312) was comprised of non-executives, executives, managers, and top management from seven major insurance firms at headquarter in the Klang Valley, Malaysia. The study found that performance appraisal, internal communication, SHRM alignment in the organization, and career planning were the human resource management best practices.